Digital Competence and CLIL: The Use of WebQuests in Bilingual Education - Martínez, Plácido E. Bazo (2019)
This paper discusses the use of WebQuests as an activity to combine competencybased learning and digitalization in a CLIL context through social tasks. In the 21st century, people need to use the knowledge they acquire in multiple scenarios. Thus, the educational system must provide learning contexts where students develop competences so that they are able to apply the knowledge they need in a culturally heterogeneous world. Integrated learning advocates the use of social tasks in bilingual scenarios. In order to solve a problem or explore an issue while creating a specific learning product, students connect different types of knowledge and thus acquire a more contextualized perspective of learning as a socially relevant activity. This kind of learning can be perceived as a bridge between the students’ educational context and daily lives. The digitalization of education is crucial for understanding how society advances and works as many of the jobs that appear in the future will require digital literacy. In this paper, an example of a WebQuest in a CLIL class in Spain is presented as a model for competency-based learning and digitalization through a social task.